PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM DESA WISATA DALAM MENANGGULANGI KEMISKINAN (STUDI DI DESA CEMPAKA KECAMATAN BUMIJAWA KABUPATEN TEGAL) - Rahmanda, Effreyza; Harsasto, Priyatno (Journal of Politic and Government Studies, 2019)
This research was conducted to explain the efforts to empower through a village tourism program in tackling poverty in the Cempaka Village, Tegal District.This research uses qualitative research methods that are descriptive in nature by giving a description of the problem systematically, carefully, in detail and in depth to reveal the facts of a problem or event. This study was conducted by requesting data from informants who were carefully selected and considered appropriate or representative in providing information about research problems. The data then explains the efforts made by community empowerment actors in overcoming poverty.The results of the study show that the government, society and the private sector have sought to empower the community in overcoming poverty in the Cempaka Tourism Village. Each actor has an important role in the empowerment process in Cempaka Tourism Village.In the future, the government, the public and the private sector need to enhance the optimal and consistent cooperation relationship in empowerment in the Cempaka Tourism Village.Keywords : Empowerment, Cempaka Tourism Village, Poverty, Actors of Empowerment